Solid medical waste management practices and awareness in COVID-19 screening stations - S.E. Alzghoul; O.A. Smadi; T. Almomani; M.B. Alzghoul; O.M. Al-Bataineh (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES:During the Coronavirus disease 2019 pandemic, an effective and efficient medical waste management plan is required to prevent disease transmission from the Coronavirus disease 2019 viral solid wastes. Screening stations are critical locations where solid Coronavirus disease 2019 wastes are created. Solid trash collection and management strategies for screening stations must be studied as they are the first point of origin for solid Coronavirus disease 2019 wastes. The goal of this study is to evaluate the level of healthcare workers' knowledge in the medical waste management field in Jordanian Coronavirus disease 2019 screening stations, with an emphasis on understanding and implementing Jordanian medical waste management protocols, by examining the awareness, perspective, and practice about the many aspects of Coronavirus disease 2019 wastes.METHODS: A study sample (n = 78) involving technicians, nurses, and physicians working at various screening stations in Jordan's public and private sectors was evaluated. From April 2021 to September 2021, a cross-sectional survey involving questionnaires was carried out. The survey included questions on medical waste management knowledge and awareness among healthcare personnel regarding the Coronavirus 2019 medical waste administrative and collection procedures. There are various limitations to this cross-sectional study that should be noted. This is a study conducted among health care employees when an overwhelming amount of coronavirus disease cases were being recorded locally and worldwide, affecting transportation ability and minimizing time spent with screening station personnel.FINDINGS: The outcomes of the first module of the questionnaire revealed a high degree of medical waste management knowledge and awareness among healthcare staff. On the other hand, nurses demonstrated the highest awareness and application of COVID-19 medical waste administrative procedures. Furthermore, the results of the third module revealed that the private sector fails to successfully execute national and international procedures, with the most significant negative responses among other categories.CONCLUSION: It was concluded that Jordan's solid waste collection and disposal methods were effectively implemented, which might aid in the virus eradication. Even though most Jordanian screening stations have effectively implemented knowledge and awareness regarding solid Coronavirus disease 2019 wastes management practices, there is a need to undertake periodic training and continuous monitoring with a specific focus on the appropriate administrative and collecting processes for both technicians, and private sector stations.